Voluntary biting behavior as a functional measure of orofacial pain in mice - Guo, Wei (Physiol Behav, 2019)
INTRODUCTION: Pain-related behavior secondary to masticatory function can be assessed with the rodent bite force model. A reduction of the bite force has been shown to be related to pain associated with the masseter muscle and jaw activity, while an increase in bite force suggests improvement of muscle function and less pain. To evaluate the usefulness of the bite force measure in studying long-lasting orofacial pain we analyzed biting parameters during prolonged myofascial pain induced by ligation injury of the masseter muscle tendon (TL) in mice. METHODS: C57BI/6 mice were habituated to bite at a pair of aluminum plates attached to a force displacement transducer. The transduced voltage signals were amplified and converted to force through calibration with a standard weight set. Voluntary biting behavior was recorded for 100 seconds/session and those with bite forces ≥ 980 mN were analyzed. Nociception was also verified with von Frey, conditioned place avoidance (CPA) tests and mouse grimace scale. Persistent orofacial pain was induced with unilateral ligation of one tendon of the masseter muscle (TL). RESULTS: To reduce interference of random bites of smaller forces, the top 5 or 15 bite forces (BF5/15) were chosen as a measure of masticatory function and related to pain behavior. Both male and female mice exhibited similar BF5/15. For the first nascent test of all mice, mean bite force was significantly and positively correlated with the body weight. However, this correlation was less clear in the latter tests (2-8 w). TL induced a reduction of BF5/15 that peaked at 1 w and returned to the baseline within 3 w. The von Frey and CPA tests indicated that mechanical allodynia/hyperalgesia persisted at the time when the BF had returned to the pre-injury level. Infusion of pain-relieving bone marrow stromal cells improved biting behavior in both male and female mice as shown by significantly increased BF5/15, compared to vehicle-treated mice. CONCLUSIONS: Mouse voluntary biting behavior can be reliably measured and quantified with a simplified setup. The bite force showed an inverse relationship with the level of pain after TL and was improved by pain-relieving manipulations. However, the injury-induced reduction of bite force peaked early and did not parallel with other measures of nociception in the later phase of hyperalgesia. The results suggest that multiple factors such as the level of habituation, cognitive motive, physical status, and feeding drive may affect random voluntary biting and confound the biting parameters related to maintained hyperalgesia.